FIBROMYALGIA AND DRY THERAPEUTIC EXERCISE. IBLIOGRAPHIC REVIEW (Cuestiones de Fisioterapia, 2019)
Background: fibromyalgia is a chronic disease of unknown etiology with high prevalence and high impact on the family, social, labor and economic level. Physical exercise has strong scientific evidence to improve the quality of life of people with fibromyalgia, but there are insufficient programs to guide physiotherapists to plan the appropriate exercise protocol. Objective: To determine some guidelines to dry exercises based on an updated bibliographic review about the treatment with exercise of patients with fibromyalgia. Material and method: search was carried out in DIALNET, Scielo, PEDro, MEDLINE databases. Words "fibromyalgia" and "exercise" were used as the search criteria. PEdro scale was used as methodological quality criterion. Results and Discussion: from 877 results obtained initially, 12 documents were selected. The studies analyzed focused mainly on aerobic, strength and stretching exercises. Aerobic exercises should be performed taking into account the maximum heart rate and progressively increase the intensity, and the same for strength exercises. Conclusions: the exercise protocol should last between 40-60 minutes, 2 or 3 times a week, including: aerobic exercises, resistance exercises, flexibility and relaxation exercises.